2019
DOI: 10.1155/2019/9154918
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Preference, and Willingness to Pay for Hepatitis B Vaccination Services among Woman of Reproductive Age in Vietnam

Abstract: Background. Hepatitis B virus (HBV) vaccine is a critical approach to prevent HBV transmission from mother to child. However, despite high HBV prevalence, evidence about the preference of women of productive age for HBV vaccine in Vietnam was constrained. This study aims to explore the preference and willingness to pay (WTP) for the HBV vaccine in Vietnamese women in productive age. Methods. A cross-sectional study was conducted in Hanoi in April 2016. A structured questionnaire was used to collect information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
6
1
1
Order By: Relevance
“…Meanwhile, only one-tenth of the study population has sought information relating to the vaccine from community health workers or healthcare staff at hospitals. Our results were consistent with the earlier studies in Vietnam regarding the vaccination of dengue fever, 27 , 28 hepatitis B, 29 and human papillomavirus. 30 These research explored that different types of mass media consisting of social media, the internet, and television were main methods to provide information about Covid-19 vaccine to the Vietnamese general population.…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, only one-tenth of the study population has sought information relating to the vaccine from community health workers or healthcare staff at hospitals. Our results were consistent with the earlier studies in Vietnam regarding the vaccination of dengue fever, 27 , 28 hepatitis B, 29 and human papillomavirus. 30 These research explored that different types of mass media consisting of social media, the internet, and television were main methods to provide information about Covid-19 vaccine to the Vietnamese general population.…”
Section: Discussionsupporting
confidence: 93%
“…Among those willing to pay, the mean maximum was US$10.30, over twice the amount found by a similar study in 2016 (108,600 VND, US$4.73). 13 When participants were asked how much they were willing to pay, differences between income levels emerged for maximum prices greater than US$4.50. We found that 50% of women from Q4 and Q5 were willing to pay a maximum price between US$9–US$18, whereas 50% of women from Q1 were willing to pay less than US$9.…”
Section: Discussionmentioning
confidence: 99%
“…A promising strategy that has been proposed to decrease rates of HBV infection transmission and improve disease control is vaccination of women of reproductive age (WRA). 13 During pregnancy, women are vaccinated to confer immunity to neonates, 14 given the risk of horizontal transmission in adulthood. However, there is a lack of randomized controlled trials on the efficacy of HBV vaccination for WRA to prevent maternal infection and consequently neonatal infection.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, we also speculated that this result might be explained by the perceived cost to the individual, with studies demonstrating that the high price of vaccines was a major cause of vaccine hesitancy, and that even if people were better informed about vaccines, the perceived high cost in terms of time, price, and availability would deter their vaccination ( 73 ). However, at this stage, there are still few pilot cities in China where girls of appropriate age can receive the domestic bivalent HPV vaccine for free, and the age is basically limited to women under 18 years old, so most women still need to pay for the HPV vaccine themselves.…”
Section: Discussionmentioning
confidence: 99%